Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1002/ceat.201400028
|View full text |Cite
|
Sign up to set email alerts
|

Transparent and Inexpensive Microfluidic Device for Two‐Phase Flow Systems with High‐Pressure Performance

Abstract: A design strategy allowing the development of an inexpensive microdevice with a cylindrical section able to work at high pressures is established. The setup combines good optical access, high-pressure resistance, homogeneous operation conditions, fast process control and detection, and the ability to generate a stable twophase flow. The experiments are conducted in the ionic liquid 1-butyl-3-methylimidazolium hexafluorophosphate and supercritical carbon dioxide flow under isothermal conditions. The two-phase f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…FormLabs clear that is compressible and transparent, but not flexible could find application in building microchannels that need to be sandwiched between two substrates for detection [13]. Venus clear that is transparent in appearance can be used for creating microchannels that involve biological samples in two-phase flow systems [42]. The proposed work focuses onto test for the compatibility of the resin to build a microfluidic device that inculcates protein, enzymatic (PCR), and cell interactions.…”
Section: Resultsmentioning
confidence: 99%
“…FormLabs clear that is compressible and transparent, but not flexible could find application in building microchannels that need to be sandwiched between two substrates for detection [13]. Venus clear that is transparent in appearance can be used for creating microchannels that involve biological samples in two-phase flow systems [42]. The proposed work focuses onto test for the compatibility of the resin to build a microfluidic device that inculcates protein, enzymatic (PCR), and cell interactions.…”
Section: Resultsmentioning
confidence: 99%
“…Pressure-resistant microfluidic chips have become of increasing interest in recent years for flow chemistry (Benito-Lopez et al 2008;Verboom 2009;Razzaq et al 2009;Trachsel et al 2008), processes involving supercritical fluids (Benito-Lopez et al 2007;Marre et al 2012;Luther and Braeuer 2012), materials science (Marre et al 2012) and also as analysis tools (Benito-Lopez et al 2005;Keybl and Jensen 2011;Dorobantu Bodoc et al 2012;Pinho et al 2014;Macedo Portela da Silva et al 2014;Gothsch et al 2015;Blanch-Ojea et al 2012;Zhao et al 2013;Ogden et al 2014). Indeed, it is well known that operating processes at high pressure modify fluid properties, which may enable enhanced kinetics, conversion and selectivity (Verboom 2009;Benito Lopez et al 2007;Kobayashi et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Some simpler glass devices based on fused silica capillaries have also been proposed for high-pressure applications (Macedo Portela da Silva et al 2014;Marre et al 2009). Marre et al (2009) showed the use of silica capillaries under pressure conditions ranging from 80 to 180 bar.…”
Section: Introductionmentioning
confidence: 99%